A method for modifying low-solid content solid waste slurry into ceramsite or sintered product raw materials

By directly mixing and homogenizing the low-solid-containing solid waste slurry with auxiliary materials, pressurized filtration to form sintered product raw materials, solving the problems of large water consumption and uneven mixing in the treatment of high-water-containing solid waste slurry, and achieving the effects of cost reduction, efficiency improvement and process simplification.

CN118373664BActive Publication Date: 2025-03-11UNIV OF SCI & TECH BEIJING
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410479793.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-19
Publication Date
2025-03-11
Estimated Expiration
2044-04-19

AI Technical Summary

Technical Problem

The water consumption of solid waste sludge such as high moisture content in the prior art is large in the treatment process of solid waste sludge such as sludge with high moisture content, making it difficult to mix evenly, and the treatment process is complex.

Method used

The low-solid-containing solid waste slurry with a solid content of 10% to 46% is discharged directly into the mixing tank as raw materials, mixed with auxiliary materials, and homogenized with the stirring process to form a modified slurry, and then filtered, and a filter cake with a moisture content of 12 to 35% is obtained as raw materials for ceramic granules or sintered products.

Benefits of technology

It reduces production costs, improves mixing efficiency and the quality of sintered products, reduces energy and water consumption, and simplifies the process flow.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118373664B_ABST
    Figure CN118373664B_ABST
Patent Text Reader

Abstract

The present invention provides a method for modifying low-solid-content solid waste slurry into a raw material for ceramsite or sintered products, which relates to the fields of industrial waste, chemical technology and building materials, and comprises the following steps: solid waste slurry with a solid content of 10% to 46% and a solid phase particle size of less than 1 mm is uniformly mixed with auxiliary materials to obtain a modified slurry; the modified slurry is filtered to obtain a filter cake, the filter cake has a moisture content of 12 to 35%, and can be directly used as a raw material for ceramsite or sintered products; at the same time, the filter cake can also be formed, dried, and roasted to obtain ceramsite or sintered products. The method of the present invention directly uses low-solid-content solid waste slurry as a raw material, directly places auxiliary materials therein for mixing and homogenizing, and then directly filters to form a raw material for ceramsite or sintered products, thereby reducing production costs, simplifying process flow, and having higher mixing efficiency. The raw material quality of sintered products after the mixed slurry is filtered is better, and the mixing energy consumption is lower.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of industrial waste and chemical industry, and in particular to a method for modifying low-solid-content solid waste slurry into ceramsite or sintered product raw materials. Background Art

[0002] In municipal administration, industry and mining, many processes discharge solid waste in the form of slurry, such as red mud, tailings, coal slime, tailings, tailings, etc. left after wet leaching and extraction of valuable elements in the smelting process, as well as municipal sludge, river sludge, and sludge formed in printing and dyeing, papermaking, material processing, dust removal, etc. The existing method of utilizing these solid wastes is to first filter these slurries in the municipal administration, industry, mining or material processing industries to form tailings, and then transport them to sintered products or ceramsite production enterprises for resource utilization.

[0003] Red mud contains a large amount of Al2O3, SiO2 and alkali metal oxides, which are the main components for preparing aluminosilicate ceramics. Therefore, red mud has potential in the preparation of ceramics. Pei Dejian et al. further studied the effect of red mud ceramics on Na + The consolidation mechanism of anorthite is found to be relatively strong compared to pyroxene. + It has a stronger consolidation effect. In ceramics with a mass fraction of 50% red mud, the dissolution rate of sodium and potassium ions is reduced by 91.6% compared with unsintered red mud. Therefore, red mud can be used to prepare ceramsite, sintered bricks or ceramic bricks in large amounts to achieve green and high-value utilization of red mud. The coordinated utilization of red mud with coal gangue, coal slime, sewage sludge containing calorific value, and hazardous solid wastes such as anode mud and carbon slag discharged during the electrolytic aluminum production process can realize the preparation of red mud ceramsite and output steam or electricity at the same time. The process of extracting alumina from bauxite itself requires a lot of steam, so the heat output of the kiln waste heat can be converted into steam, thereby achieving synergistic coupling with the material flow and energy flow of the alumina plant. It can be seen that the preparation of sintered materials such as ceramsite is an effective way to utilize red mud in a green, low-carbon, high-value and large-scale manner.

[0004] The treatment of urban domestic sewage will produce a large amount of sewage sludge with a very high water content, which has become one of the major environmental problems that must be faced in the process of rapid urbanization. The existing sewage sludge disposal methods such as landfill, composting, and incineration are either incompletely harmless or too costly to dispose of the rapidly growing sewage sludge. According to the requirements of shale building materials for raw materials and the characteristics of the firing process, high-water-content sewage sludge is mixed with shale from a wide range of sources, and the water in the sewage sludge is used as the water that must be added in the production process of shale building materials. At the same time, the organic matter in the sewage sludge is used to supplement the calorific value of shale building materials during the firing process, making the use of sewage sludge in the preparation of shale building materials have technical, economic and environmental advantages.

[0005] However, the methods in the prior art have the following problems: 1) The tailings or sludge raw materials have a high water content, and they need to be dried in advance before being mixed and ground as ingredients, which consumes a lot of energy; 2) Even if the extrusion molding process is adopted, these high-water-content sludge or tailings raw materials need to be stirred and mixed with auxiliary materials in advance. The existing stirring equipment is not efficient in mixing and homogenizing the wet materials, and it also consumes a lot of capacity; in particular, the sludge or tailings are easy to compact after filtration, and it takes energy to break them up. The dispersed particles are far less dispersed than the suspended particles in the slurry, and the particle size is large, making it difficult to fully mix them with the auxiliary materials. 3) During the mixing and mixing of the wet materials, as the moisture content of the auxiliary materials or mud materials fluctuates, it is necessary not only to test the moisture content, but also to add water during the mixing process of the wet materials to control their moisture content, which increases the complexity of the process and wastes water resources. Summary of the invention

[0006] The present invention provides a method for modifying low-solid content solid waste slurry into ceramsite or sintered product raw materials to solve the technical problems in the prior art of large water consumption, difficulty in uniform mixing and complex treatment process during the treatment of high-water content solid waste slurry such as sludge and tailings.

[0007] In order to solve the above-mentioned invention object, the technical solution provided by the present invention is as follows:

[0008] A method for modifying low-solid content solid waste slurry into ceramsite or sintered product raw materials, comprising the following steps:

[0009] S1. Discharge low-solid-content solid waste slurry with a solid content of 10% to 46% and a solid phase particle size of less than 1 mm directly into a mixing tank as a raw material without being subjected to treatment methods such as filter pressing and drying, and at the same time add auxiliary materials to the mixing tank, mix and homogenize the slurry through a stirring process, thereby modifying the slurry and obtaining a modified slurry;

[0010] S2, filtering the modified slurry to obtain a filter cake, wherein the water content of the filter cake is 12-35%;

[0011] S3. The filter cake can be used as the raw material of ceramsite or sintered products; or it can be directly formed, dried and roasted to obtain ceramsite or sintered products.

[0012] Preferably, the ratio of the solid phase dry basis mass of the solid waste slurry to the solid phase dry basis mass of the auxiliary material in S1 is 1:1 to 9:1.

[0013] Preferably, the solid phase dry matrix in S1 mainly contains silicon oxide and aluminum oxide, and the sum of their percentages is 46-71%.

[0014] Preferably, the solid phase particles in the solid waste slurry can be suspended in the liquid phase under stirring conditions. The solid waste slurry in S1 includes three equally divided regions, namely, upper, middle and lower regions from top to bottom, and the difference in solid content between adjacent regions is less than 5%.

[0015] Preferably, the solid waste slurry in S1 is one of red mud slurry, industrial sludge, slurry after wet mineral processing, and can also be tail liquid slurry after wet extraction of valuable elements from hazardous solid waste, one of the slurries of secondary slurry of dry or stockpiled solid waste, and municipal sludge, etc.

[0016] For the red mud slurry in the alumina industry, auxiliary materials are directly added to mix and homogenize, and then filter pressing is performed. The filtrate after filter pressing is returned to the alumina plant for recycling. For tailings or tailing mud from valuable element flotation or wet magnetic separation, auxiliary materials are directly added to the slurry and mixed and homogenized, and then filter pressing is performed. The filtrate after filter pressing is returned to the main process of flotation / magnetic separation or wet grinding for recycling. Taking advantage of the secondary pulping of stored solid waste, the secondary pulping slurry is mixed and homogenized with auxiliary materials, and then filter pressing is performed. The filtrate after filter pressing is returned to the secondary pulping process for recycling.

[0017] Preferably, the auxiliary material in S1 is a mineral such as shale, quartz, or clay minerals, and the solid waste can be a mineral or solid waste powder of industrial solid waste with high silicon and aluminum components such as coal gangue, fly ash, and gasified slag, or a mixed powder of multiple minerals and / or solid wastes.

[0018] Preferably, the particle size of the auxiliary material in S1 is less than 2 mm.

[0019] Preferably, the fluctuation rate of the key indicator sampled at any two points in the modified slurry area in S1 is less than or equal to 10%.

[0020] Preferably, the key indicators refer to the content of silicon oxide, aluminum oxide, iron oxide, calcium oxide, magnesium oxide, as well as solid content, calorific value, and loss on ignition rate.

[0021] Preferably, the forming in S3 is granulation, and after granulation, ceramsite green balls are obtained, and the average strength of the ceramsite green balls is greater than 150 N. The particle size of the ceramsite green balls is 5 to 20 mm, and the sintered ceramsite can be used as ceramic raw materials, refractory raw materials, cement admixtures or concrete admixtures, moisturizing ceramsite, or ecological soil raw materials.

[0022] The process method of the present invention couples the processes between different industries, reduces the processes and energy consumption, and promotes the green and low-carbon transformation and upgrading of the industry. Specifically, the solid waste slurry with low solid content in the municipal, industrial, mining and other industries is directly used as the raw material for the subsequent preparation of sintered products. Compared with the existing process of first filtering the low solid content solid waste slurry, drying it to form a filter cake with a certain moisture content, and then mixing the filter cake with other auxiliary materials with water to form the raw material for sintered products; this process directly places the auxiliary materials in the low solid content solid waste slurry for mixing and homogenization, and then directly filters it to form the raw material for sintered products; it transforms the original solid waste discharge enterprise into a production enterprise of sintered product raw materials, and allows building materials enterprises to directly use the raw materials after filtering, thereby reducing production costs.

[0023] The method of the present invention can better meet the requirements of solid waste utilization for full mixing of components and quality assurance. Sludge and tailings solid waste usually contain components such as alkali metals, heavy metals and / or organic matter. Compared with traditional raw materials such as shale, clay or slag, it is more necessary to fully mix these solid wastes with auxiliary materials so that they can fully react during the firing process and consolidate the alkali metal and heavy metal ions. Only then can they be fully dispersed and completely decomposed and burned organic matter, so that the entire product component reacts evenly and fully, and harmful components such as alkali metal ions, free calcium oxide or heavy metal ions are well consolidated, and the overall performance is optimized. The solid waste particles in the slurry are small and suspended in the liquid, with the highest dispersion and the particle size being its true particle size; after the auxiliary materials also form a slurry, the more difficult solid-solid mixing process of wet material to wet material or dry material is changed to a simple liquid-liquid mixing or liquid-solid mixing, so the mixing efficiency is higher, the quality of the raw materials of the sintered products after the mixed slurry is pressed and filtered is better, and the mixing energy consumption is lower.

[0024] The method of the present invention is applied to solid waste slurry discharge enterprises, which can ensure the quality of filter cakes sold by adjusting their own processes. Fluctuations in the composition and moisture content of solid waste are a major factor that makes it difficult to utilize. In solid waste discharge enterprises, the composition fluctuations, moisture content, etc. of the solid waste slurry can be adjusted by changing the type of auxiliary materials or the corresponding discharge process parameters according to changes in the process during the production process, thereby facilitating the control of the moisture and composition of the sintered product raw materials after filter pressing. This makes it easier to coordinate solid waste utilization with the source of production. Sintered product enterprises directly use raw materials with stable moisture and composition, and no further batching process is required, which is not only low-cost, but also lowers the threshold for resource utilization enterprises. Therefore, the present invention is conducive to controlling the quality of filter cakes, improving process efficiency, and reducing the utilization cost of sludge or tailings solid waste in sintered product enterprises, thereby promoting the resource utilization of such solid waste.

[0025] The present invention determines the range of slurries that can be mixed. Not all slurries are suitable for direct modification. Appropriate components (the modified mixed slurry satisfies the sum of the mass percentage of solid phase dry silicon oxide and aluminum oxide of 46-71%) and water-solid ratio (solid content of 10%-46% and low solid content solid waste slurry with solid phase particle size less than 1mm) are required to meet the suspension, mixing and subsequent sintering processes.

[0026] Compared with the prior art, the method of the present invention has at least the following beneficial effects: the method of the present invention directly uses low-solid content solid waste slurry as raw material, directly places auxiliary materials therein for mixing and homogenization, and then directly filters to form sintered product raw materials, thereby reducing production costs; using low-solid content solid waste slurry as raw material, the mixing efficiency is higher, the quality of the sintered product raw materials after the mixed slurry is filtered, and the mixing energy consumption is lower; the process of the present invention realizes the direct preparation of solid waste slurry formed in the wet process flow of waste-producing enterprises as raw materials for building materials production, greatly shortens the production process of solid waste building materials, saves energy and reduces carbon emissions, reduces water consumption, significantly reduces the production cost of solid waste building materials, realizes the coupling between the solid waste emission industry and the sintered product industry, and will further promote the green and low-carbon development of solid waste production and emission enterprises and building ceramics enterprises. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a flow chart of the pretreatment of low-solid content solid waste slurry in traditional industries in the prior art;

[0028] Figure 2 This is a flow chart of using solid waste filter cake to prepare sintered products in the sintered products industry in the prior art;

[0029] Figure 3 The present invention is a flowchart of a method for modifying a low-solid content solid waste slurry into a raw material for expanded clay or sintered products in Example 1 of the present invention. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solution and advantages of the embodiment of the present invention clearer, the technical solution of the embodiment of the present invention will be clearly and completely described below. Obviously, the described embodiment is a part of the embodiment of the present invention, not all of the embodiments. Based on the described embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] Example 1

[0032] The present embodiment provides a method for modifying low-solid content solid waste slurry into ceramsite or sintered product raw materials, with red mud slurry as solid waste slurry, the solid content of the red mud slurry is 26% and the particle size is less than 100 microns, coal gangue powder is an auxiliary material, and the dry basis mass ratio of red mud to coal gangue is 3:2. After the coal gangue is ground, it passes through a 1mm sieve, and the red mud slurry is discharged into a mixing pool, and then the ground powder is added to the red mud slurry through a hopper, and the stirring paddle in the red mud slurry is stirred, mixed and homogenized. The modified mixed slurry satisfies the sum of the mass percentages of silicon oxide and aluminum oxide on a solid dry basis of 56%. The solid suspension performance of the homogenized slurry is good. After the key indicators are tested, the fluctuation of the components in different regions of the homogenized slurry is less than ±5%. After the slurry is filtered, the water content of the solid waste filter cake is 20%. The extrusion granulator is further used to extrude cylindrical particles with a diameter of 10mm and a length of 10-15mm. The average strength of a single ball is greater than 150N. After shaping, the particles are sent to the roasting kiln for firing. After firing, the cylindrical compressive strength of the ceramsite is 16MPa and the water absorption rate is 2.3%, which meets the requirements of the national standard for light aggregates (GB / T17431.1-2010) that the cylindrical compressive strength shall not be less than 5.0MPa. At the same time, the filtrate after the filter press meets the reuse requirements of the alumina plant and can be returned to the alumina plant for recycling.

[0033] The flow chart of the pretreatment of low solid content solid waste slurry in the traditional industry in the prior art is as follows Figure 1 In the prior art, the sintered products industry uses solid waste filter cakes to prepare sintered products. Figure 2 , a flow chart of a method for modifying a low-solid content solid waste slurry into a raw material for ceramsite or sintered products in this embodiment, as shown in Figure 3 . It can be seen that the method of the present invention directly places the auxiliary materials into the low-solid content solid waste slurry for mixing and homogenization, and then directly presses and filters to form the raw materials of ceramsite or sintered products, and then forms, dries and roasts them to obtain ceramsite or sintered products. The coupling between the solid waste discharge industry and the sintered product industry is realized, which will further promote the green and low-carbon development of solid waste production and discharge enterprises and building materials enterprises. .

[0034] Example 2

[0035] The present embodiment provides a method for modifying low-solid content solid waste slurry into ceramsite or sintered product raw materials. Red mud slurry is used as solid waste slurry, the solid content of the red mud slurry is 33%, and the particle size is less than 150 microns; a mixture of coal gangue and slag powder in a ratio of 1:1 is used as an auxiliary material, and the dry basis mass ratio of red mud to auxiliary material is 4:1. The coal gangue and slag are crushed and passed through a 2mm sieve, and the red mud slurry is discharged into a mixing pool, and then the ground powder is added to the red mud slurry through a hopper, and stirred, mixed and homogenized through a stirring process. The modified mixed slurry satisfies the sum of the mass percentages of silicon oxide and aluminum oxide on a solid dry basis of 51%. The solid suspension performance of the homogenized slurry is good. After the key indicators are tested, the fluctuation of the components in different regions of the homogenized slurry is less than ±5%. After the slurry is filtered, the water content of the solid waste filter cake is 22%. The extruder and cutter are further used to form 290×190×90mm brick green body. The green body flexural strength is 1.8-2.2MPa. Then it is sent to the tunnel drying kiln and the tunnel firing kiln for firing. The average compressive strength of the brick after firing is 83MPa. The finished product performance after firing is qualified and meets the national standard for sintered pavement bricks (GB / T 26001-2010). The average flexural strength of SX-type sintered pavement bricks is not less than 55MPa. At the same time, the filtrate after the filter press meets the reuse requirements of the alumina plant and can be returned to the alumina plant for recycling.

[0036] Example 3

[0037] This embodiment provides a method for modifying low-solid content solid waste slurry into ceramsite or sintered product raw materials, using desulfurization tail mud slurry as solid waste slurry, the solid content of desulfurization tail mud is 35%, the size of solid phase particles is 2mm, and the kiln slag slurry and fly ash powder after wet grinding iron selection are used as auxiliary materials, and the dry basis mass ratio of desulfurization tail mud to auxiliary materials is 3:2. Kiln slag and fly ash with a particle size of less than 180 mesh are added to the red mud slurry at the same time, and the mixture is stirred and homogenized through a stirring process. The mixed slurry after homogenization satisfies the sum of the mass percentage of silicon oxide and aluminum oxide on a solid dry basis of 48%, and a homogenized slurry with a component volatility of less than ±7% is obtained. After the slurry is filtered, the moisture content of the solid waste filter cake is 18%, and an extrusion granulator is further used to extrude cylindrical particles with a diameter of 12mm and a length of 10-16mm, and the average single ball raw ball strength is greater than 155N. After being shaped, the particles are sent to the roasting kiln for firing. After firing, the cylinder pressure strength of the ceramsite is 10.4MPa and the water absorption rate is 3.3%, which meets the requirements of the national standard for light aggregate (GB / T17431.1~2010), which stipulates that the cylinder pressure strength of high-strength ceramsite shall not be less than 6.5MPa. The filtrate after filtration is recycled by the solid waste discharge enterprise.

[0038] Example 4

[0039] The present embodiment provides a method for modifying low-solid content solid waste slurry into ceramsite or sintered product raw materials, using industrial tailings after copper tailings grinding and flotation to extract copper as solid waste slurry, with a solid content of 40% and a particle size of 180mm. Construction debris is used as an auxiliary material, and the dry basis mass ratio of tailings to auxiliary materials is 9:1. The construction debris is secondary slurried, with a solid content of 66% and a particle size of less than 2mm. The copper tailings tailings and construction debris slurry are stirred and homogenized through a stirring process, and the mixed slurry after homogenization satisfies the sum of the mass percentage of silicon oxide and aluminum oxide on a solid basis of 62%, and a homogenized slurry with a component volatility of less than ±6% is obtained. After the slurry is filtered, the moisture content of the solid waste filter cake is 12%, and an extrusion granulator is further used to extrude cylindrical particles with a diameter of 15mm and a length of 10-15mm, and the average strength of a single ball is greater than 197N. After being shaped, the particles are sent to the roasting kiln for firing. After firing, the cylinder pressure strength of the ceramsite is 12.7MPa and the water absorption rate is 6.3%, which meets the requirements of the national standard for light aggregate (GB / T17431.1~2010), which stipulates that the cylinder pressure strength of high-strength ceramsite shall not be less than 6.5MPa. The filtrate after filtration is recycled into the solid waste discharge enterprise.

[0040] Example 5

[0041] The present embodiment provides a method for modifying low-solid content solid waste slurry into ceramsite or sintered product raw material, wherein the tailings slurry after flotation copper extraction is used as solid waste slurry, and the solid content is 45%. Shale and tailings fine powder are used as auxiliary materials, and the particle size is less than 180 mesh. The dry basis mass ratio of copper slag tailings to auxiliary materials is 7:3. The auxiliary materials are added to the copper slag tailings slurry with a particle size of less than 250 mesh, and the mixture is stirred, mixed and homogenized through a stirring process. The mixed slurry after homogenization satisfies the sum of the mass percentage of silicon oxide and aluminum oxide on a solid dry basis of 71%, and a homogenized slurry with a component volatility of less than ±10% is obtained, and the residue of the obtained slurry passing through an 80-mesh sieve does not exceed 1% (mass fraction). The moisture content of the slurry after filter pressing is 13%. It is further formed into 290×190×90mm bricks by extruder and cutter. The green bricks have a flexural strength of 1.8-2.2MPa. Then it is sent to tunnel drying kiln and tunnel firing kiln for firing. The average compressive strength of the bricks after firing is 66MPa. The performance of the fired bricks is qualified and meets the requirements of the national standard for fired pavement bricks (GB / T 26001-2010). The average flexural strength of SX-type fired pavement bricks is not less than 55MPa. The filtrate after filter pressing meets the requirements of returning to flotation for copper extraction, so the filtrate is returned to the flotation process for copper extraction for recycling.

[0042] Example 6

[0043] The present embodiment provides a method for modifying low-solid content solid waste slurry into ceramsite or sintered product raw materials. The red mud slurry formed after the secondary pulping of the stockpiled red mud is used as the solid waste slurry, the solid content of the red mud slurry is 35%, the particle size of the solid phase particles is 150mm, the mixture of fly ash and slag powder is used as the auxiliary material, and the dry basis mass ratio of red mud to auxiliary material is 6:4. After the coal gangue and slag are ground and passed through a 2mm sieve, the red mud slurry is discharged into the mixing pool, and then the ground powder is added to the red mud slurry through the hopper, and stirred, mixed and homogenized by a stirring process. The modified mixed slurry satisfies the sum of the mass percentages of silicon oxide and aluminum oxide on a solid dry basis of 52%. The solid suspension performance of the homogenized slurry is good. After the key indicators are tested, the fluctuation of the components in different regions of the homogenized slurry is less than ±5%. After the slurry is filtered, the water content of the solid waste filter cake is 19%. The extruder and cutter are further used to form 290×190×90mm brick green body with a green body flexural strength of 1.8-2.2MPa. Then it is sent to the tunnel drying kiln and tunnel firing kiln for firing. The average compressive strength of the brick after firing is 85MPa. The performance of the sintered brick product is qualified and meets the requirements of the national standard for sintered pavement bricks (GB / T 26001-2010). The average flexural strength of SX-type sintered pavement bricks is not less than 55MPa. At the same time, the filtrate after the filter press is returned to the secondary pulping link of the red mud storage for recycling.

[0044] Example 7

[0045] The present embodiment provides a method for modifying low-solid content solid waste slurry into ceramsite or sintered product raw materials. The sludge produced and discharged from the steel mill is used as the solid waste slurry, the solid content of the sludge is 22%, the solid phase particle size is 150mm, the mixture formed by mixing clay and shale in a ratio of 1:1 is used as the auxiliary material, and the dry basis mass ratio of the steel rolling sludge to the auxiliary material is 8:2. The mixture of clay and shale is ground and passed through a sieve with a particle size of 2mm. The sludge produced and discharged from the steel mill is discharged into the mixing tank, and then the ground auxiliary material is added to the sludge through the hopper, and the stirring process is used to stir, mix and homogenize. The modified mixed slurry satisfies the sum of the mass percentages of silicon oxide and aluminum oxide on a solid dry basis of 56%. The solid suspension performance of the slurry after homogenization is good. After the key indicators are tested, the fluctuation of the components in different regions of the homogenized slurry is less than ±5%. After the slurry is filtered, the water content of the solid waste filter cake is 19%. The extruder and cutter are further used to form 290×190×90mm brick green body with a green body flexural strength of 1.8-2.2MPa. Then it is sent to the tunnel drying kiln and tunnel firing kiln for firing. The average compressive strength of the brick after firing is 72MPa. The performance of the sintered brick product is qualified and meets the national standard for sintered pavement bricks (GB / T 26001-2010). The average flexural strength of SX-type sintered pavement bricks is not less than 55MPa. At the same time, the filtrate after the filter press meets the reuse requirements of the steel plant and can be returned to the steel plant for recycling.

[0046] Example 8

[0047] The present embodiment provides a method for modifying low-solid content solid waste slurry into ceramsite or sintered product raw materials. Magnetic separation wet-ground steel slag is used as solid waste slurry, the solid content of the steel slag is 46%, and the solid phase particle size is 150mm; the mixture formed by mixing slag and shale in a ratio of 1:1 is used as auxiliary material, and the dry basis mass ratio of steel slag to auxiliary material is 1:1. The mixture of slag and shale is ground and passed through a sieve with a particle size of 2mm. The magnetic separation wet-ground steel slag is discharged into a mixing pool, and then the ground auxiliary material is added to the steel slag tailings through a hopper, and stirred, mixed and homogenized through a stirring process. The modified mixed slurry satisfies the sum of the mass percentages of silicon oxide and aluminum oxide on a solid phase dry basis of 46%. The solid phase suspension performance of the homogenized slurry is good. After the key indicators are tested, the fluctuation of the components in different regions of the homogenized slurry is less than ±5%. After the slurry is filtered, the water content of the solid waste filter cake is 15%. The extrusion granulator is further used to extrude cylindrical particles with a diameter of 12mm and a length of 8-16mm. The average strength of a single ball is greater than 238N. After shaping, the particles are sent to the roasting kiln for firing. After firing, the cylinder pressure strength of the ceramsite is 11.2MPa and the water absorption rate is 8.6%, which meets the requirements of the national standard for light aggregates (GB / T17431.1-2010) that the cylinder pressure strength of high-strength ceramsite shall not be less than 6.5MPa. At the same time, the filtrate after the filter press meets the reuse requirements of the steel plant and can be returned to the steel plant for recycling.

[0048] Example 9

[0049] The present embodiment provides a method for modifying low-solid content solid waste slurry into ceramsite or sintered product raw materials. Municipal sludge is used as solid waste slurry, the municipal sludge has a solid content of 10%, and the solid phase particle size is 150mm; urban tailings and slag are mixed in a ratio of 1:1 as auxiliary materials, and the mixture of urban tailings and slag is ground and passed through a 2mm sieve. The dry basis mass ratio of municipal sludge to auxiliary materials is 3:2. The municipal sludge is discharged into a mixing tank, and the mixture of urban tailings and slag of corresponding mass is added to the municipal sludge through a hopper, and stirred, mixed and homogenized through a stirring process. The modified mixed slurry satisfies the sum of the mass percentages of silicon oxide and aluminum oxide on a solid dry basis of 48%. The solid suspension performance of the homogenized slurry is good. After the key indicators are tested, the fluctuation of the components in different regions of the homogenized slurry is less than ±5%. After the slurry is filtered, the water content of the solid waste filter cake is 35%. The extrusion granulator is further used to extrude cylindrical particles with a diameter of 12mm and a length of 10-19mm. The average strength of a single ball is greater than 155N. After shaping, the particles are sent to the roasting kiln for firing. After firing, the cylinder pressure strength of the ceramsite is 7.05MPa and the water absorption rate is 9.7%, which meets the requirements of the national standard for light aggregates (GB / T17431.1-2010), which stipulates that the cylinder pressure strength of high-strength ceramsite shall not be less than 6.5MPa. The filtrate after the filter press enters the treatment and meets the discharge standards.

[0050] Example 10

[0051] The present embodiment provides a method for modifying low-solid content solid waste slurry into ceramsite or sintered product raw materials. A wet magnetic separation tailings slurry is used as solid waste slurry, the solid content of the magnetic separation tailings is 40%, and the particle size is less than 1mm. Clay with a particle size less than 180 mesh and fly ash are mixed in a dry basis mass ratio of 1:3 as auxiliary materials. The auxiliary materials are added to the tailings slurry and stirred and homogenized through a stirring process. The homogenized mixed slurry satisfies the sum of the mass percentages of solid phase dry basis silicon oxide and aluminum oxide of 52%, and a homogenized slurry with a component volatility of less than ±7% is obtained. After the slurry is filtered, the moisture content of the solid waste filter cake is 18%, and an extrusion granulator is further used to extrude cylindrical particles with a diameter of 12mm and a length of 10-15mm, and the average single ball raw ball strength is greater than 155N. After the particles are shaped, they are sent to the roasting kiln for firing. After firing, the cylinder pressure strength of the ceramsite is 9.68MPa and the water absorption rate is 6.3%, which meets the requirements of the national standard for light aggregate (GB / T17431.1-2010) that the cylinder pressure strength of high-strength ceramsite shall not be less than 6.5MPa. The filtrate after filtration is recycled by the solid waste discharge enterprise.

[0052] Comparative Example

[0053] This comparative example is similar to Example 1, using the red mud filter cake formed after the red mud slurry is filtered as the raw material, and coal gangue powder as the auxiliary material. The red mud and coal gangue are dried separately, and then the ingredients are ground into particles at a dry basis mass ratio of 3:2 until the raw material particle size is less than 1 mm. Water is then added to form a wet powder with a water content of 13%, which is further stirred and homogenized and extruded into granules to extrude cylindrical particles with a diameter of 10 mm and a length of 10 to 15 mm. The average strength of a single ball is about 120 N. After the particles are shaped, they are sent to a roasting kiln for firing. After firing, the cylindrical compressive strength of the ceramsite is 6.2 MPa and the water absorption rate is 9.3%. Although it meets the national standard for lightweight aggregates (GB / T17431.1-2010) that the cylindrical compressive strength shall not be less than 5.0 MPa, compared with the method of directly using red mud slurry to modify and prepare ceramsite raw materials in Example 1, the mechanical properties are significantly worse, the process is complicated, the mixing efficiency is poor, there is an alkali return phenomenon, the quality of the raw materials of the sintered products after the mixed slurry is filtered out is poor, the mixing energy consumption is higher, there is an extra raw material drying link and energy consumption, and the production cost is high.

[0054] The above are only specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. The protection scope of the present invention shall be based on the protection scope of the claims.

Claims

1. A method for modifying low-solid content solid waste slurry into ceramsite or sintered product raw materials, characterized in that: The following steps are involved: S1. A red mud slurry having a solid content of 26% and a particle size of less than 100 μm is uniformly mixed with coal gangue to obtain a modified slurry, wherein the solid dry basis mass ratio of the red mud slurry to the solid dry basis mass ratio of the coal gangue is 3:2, and the sum of the solid dry basis mass percentages of silicon oxide and aluminum oxide in the modified slurry is 56%; S2, filtering the modified slurry to obtain a filter cake, wherein the water content of the filter cake is 20%; S3, the filter cake can be used as the raw material of ceramsite or sintered products or directly formed, dried and calcined to obtain ceramsite or sintered products.

2. The method for modifying low-solid content solid waste slurry into ceramsite or sintered product raw materials according to claim 1, characterized in that: The red mud slurry in S1 includes three equally divided regions, namely, upper, middle and lower regions, from top to bottom, and the difference in solid content between adjacent regions is less than 5%.

3. The method for modifying low-solid content solid waste slurry into ceramsite or sintered product raw materials according to claim 1, characterized in that: The particle size of the coal gangue described in S1 is less than 2 mm.

4. The method for modifying low-solid content solid waste slurry into ceramsite or sintered product raw materials according to claim 1, characterized in that: The fluctuation rate of the key index sampled at any two points in the modified slurry area described in S1 is less than or equal to 10%.

5. The method for modifying low-solid content solid waste slurry into ceramsite or sintered product raw materials according to claim 4, characterized in that: The key indicators refer to the content of silicon oxide, aluminum oxide, iron oxide, calcium oxide, magnesium oxide as well as solid content, calorific value and loss on ignition rate.

6. The method for modifying low-solid content solid waste slurry into ceramsite or sintered product raw materials according to claim 1, characterized in that: The forming described in S3 is granulation, and after granulation, ceramsite green balls are obtained, and the average strength of the ceramsite green balls is greater than 150N.

Citation Information

Patent Citations

  • Sewage sludge shale ceramic particle and preparation method thereof

    CN101186485A

  • Method for synergistically firing ceramsite by using river and lake bottom mud and municipal sludge

    CN117776765A